IMPACT OF THE ENVIRONMENT AND ECONOMIC SUSTAINABILITY WHEN USING BIODIESEL IN COMBUSTION ENGINES (Estudos do CEPE, 2021)
This paper presents a proposal for a computer simulation model to reduce costs, water pollution and CO2 emissions, including the collection of urban waste in the central region of Rio Grande do Sul state. Will use various percentages of biodiesel, which together diesel percentages will form a fuel with less impact on the environment. To define variables and their interrelationships used by theoretical bases such as bibliographic research and applications of the cooking oil post-use waste generation process. To evaluate the possibility of generating a new fuel that can be used by vehicles used for total waste collection in the central region of the state, two scenarios were generated: one scenario based on the current situation of waste collection and another; proposed scenario, with best reapproval practices. The results obtained through simulation show that besides the great reduction of environmental impact, the recycling process brings a significant economic gain due to the reduction of costs with fuel acquisition. The simulated time horizon was 10 (ten) years and was used by Vensim software for the development of the simulation.